Human-derived natural antibodies: biomarkers and potential therapeutics. (January 2015) - Xu, Xiaohua; Ng, Sher May; Hassouna, Eamonn; Warrington, Arthur; Oh, Sang-Hyun; Rodriguez, Moses
ABSTRACT : The immune system generates antibodies and antigen-specific T-cells as basic elements of the immune networks that differentiate self from non-self in a finely tuned manner. The antigen-specific nature of immune responses ensures that normal immune activation contains non-self when tolerating self. Here we review the B-1 subset of lymphocytes which produce self-reactive antibodies. By analyzing the IgM class of natural antibodies that recognize antigens from the nervous system, we emphasize that natural antibodies are biomarkers of how the immune system monitors the host. The immune response activated against self can be detrimental when triggered in an autoimmune genetic background. In contrast, tuning immune activity with natural antibodies is a potential therapeutic strategy.